Desain Proses Produksi Survival Knife dengan Metode Operation Process Chart di Perusahaan Manufaktur - Amelia Laksmi; Renanda Nia Rachmadita; Rina Sandora (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Manufacturing Company is one of the manufacturing industry in Surabaya focusing onengineering field, in producing machinary. One institution give a challenge to this company toproduce 10.000 pcs Survival Knives. Complex technique and limited machinary make it difficult forthis Manufacturing Company in Designing Production Process. Cycle time production, quantities andcost of production are considered in Designing Production Process. Operation Process Chart help usto visualize flow production process from raw material until finished good product. Production timecould see with Bar Chart Method its about 48 days left with paralel process. Researcher makes twoalternative concepts of designing production process. Concept selection is done trough two ways.First, based on the most point and second with Matrix Pugh Concept Selection. The result of thisresearch shows that â€œDesigning Production Process Concept 2â€ is choosen because it has moreaverage quantity about 56 pcsand cost o production is lower than â€œDesigning Production ProcessConcept 1â€ its about Rp.1.554.581.900,-. Concept 2 is better in cycle time production about 12 daysmore than concept 1